Effect of Student Teams Achievement Division and Think-Pair-Share on Students' Achievement in Reading Comprehension - Eucharia Okwudilichukwu Ugwu (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2019)
Abstract The study investigated the effect of two cooperative learning strategies, Student Teams-Achievement Divisions (STAD) and Think-Pair-Share (TPS) on senior secondary school students' achievement in reading comprehension in Vandeikya Local Government Area, Benue State, Nigeria. A total of 78 students (43 males and 35 females), drawn from three secondary schools participated in the study. Experimental and control conditions were randomly assigned to the three intact classes: EG1 (STAD), EG2 (TPS) and CG (Control Group). The instrument used was Reading Comprehension Achievement Test (r=0.784). Data were analyzed using Mean, Standard Deviation and Analysis of Covariance (ANCOVA). The results show higher achievement gains for students in the EG1 and EG2 over those of the CG, but not across gender. The findings support the existing evidence on the efficacy of cooperative learning over the traditional teaching method. English language teachers will therefore find the two techniques useful in teaching reading comprehension.   Keywords: cooperative learning, Student Teams-Achievement Divisions, Think-Pair-Share, academic achievement, reading comprehension